Magnitude of Effect of Rural Banditry on IFAD-CASP Participating Crop Producers in Zamfara State, Nigeria - Sanchi, I. D; Saadu, U; Kaka, Y.; Muhammad, A. (Discoveries in Agriculture and Food Sciences, 2023)
The researched analyzed the extent/ magnitude of effects of rural banditry on IFAD-CASP participating crop producers in Zamfara state, Nigeria. Interview schedule and focused group discussion (FGD) were used to collect data from 360 respondents that were selected for the study. A multi stage and simple random sampling technique was used in selecting the respondents. Descriptive statistical tools (mean, percentages, frequency distribution and ranking) were used for data analysis. The results of the study reveals that majority of the respondents were married with an average household size of 8 persons and income level of less than N 20,000/month. Most of the respondents (50%) indicate that the conflict is very severe resulting to great economic, physical and social effects on the respondents. Majority (70%) of the respondents’ perceived western agricultural zone of the study location as intense conflict area. The results of ranking of effect of rural banditry on IFAD-CASP in the study area, indicates poor participation, increased rural poverty, poor supervision of programme, poor economic growth and poor information dissemination were ranked 1st, 2nd, 3rd, and 4th respectively. Based on the finding of the study, it could be concluded that rural banditry poses poor economic growth, increased rural poverty, poor participation, and poor programme implementation and induces fear and uncertainty. The study therefore, recommend that urgent recruitment of adequate security personnel to patrol the porous borders, prompt enrollment of the vulnerable into government social investment programmes, organize training/seminars for peace building purpose.